A multidisciplinary approach to investigate the manifestations of Diffuse Idiopathic Skeletal Hyperostosis (DISH) in modern South African skeletal remains - L'Abbe, Ericka Noelle (University of Pretoria, 2021)
Thesis (PhD (Anatomy))--University of Pretoria, 2020.